Flash Based Interactive Multimedia Development to Increasing Learning Outcomes of Participants in High School in Materials Excretory System - Puspitasari, Rini; Miarsyah, Mieke; Rusdi, Rusdi (International Journal for Educational and Vocational Studies, 2020)
This study aims to develop flash-based interactive multimedia for class XI students as a media in the learning process in Pandeglang 2 High School. This flash-based interactive multimedia is used to facilitate students in mastering excretion system material. This research includes development research with reference to borg and gall. Products developed based on preliminary research are flash-based interactive multimedia for students of class XI containing excretory system material. The trial subjects in this development research were expert subjects, namely excretory system experts, learning media experts, linguists, and sample subjects of high school class XI students as potential product users. Determination of the sample subject using random sampling, which consists of 15 students for the main field trial, and 90 students for the operational field test. The results of the development research are: (1) The learning media development model is carried out through several stages, namely conducting information gathering, product planning developed, early flash-based multimedia product forms, early stage field testing, flash-based revision of early multimedia products, main field tests , revisions to operational products, operational field tests, final product revisions, and operational field tests (2) Learning media are able to have a positive impact on the learning outcomes of class XI students at SMAN 2 Pandeglang by obtaining a percentage of 76.58% with criteria "Good."